Concrete-filled high strength steel tube stub columns after exposure to fire: testing, numerical modelling and design - Zhong, Yukai (2022)
This paper reports experimental and numerical investigations into the structural behaviour and residual capacity of concrete-filled high strength steel tube (CFHST) stub columns after exposure to fire. The experimental investigation was conducted on twelve square CFHST stub column specimens after exposure to the ISO-834 standard fire for 15 min, 30 min and 45 min and four reference specimens at ambient temperature. The test results, including failure loads, load–end shortening curves, initial compressive stiffnesses and failure modes, were fully reported and discussed. A numerical investigation was subsequently conducted, where thermal and mechanical finite element models were developed and validated against the test results, and afterwards used to performed parametric studies to generate further numerical data over a wide range of cross-section dimensions. Owing to the absence of design codes for composite structures after exposure to fire, the relevant ambient temperature design rules, as set out in European code, American specification and Australian/New Zealand standard, were evaluated, using post-fire material properties, for their applicability to post-fire CFHST stub columns, based on the test and numerical data. The evaluation results revealed that all the three design codes generally yield accurate failure load predictions for CFHST stub columns after exposure to fire.